2022
DOI: 10.1098/rstb.2021.0431
|View full text |Cite
|
Sign up to set email alerts
|

Female cooperative labour networks in hunter–gatherers and horticulturalists

Abstract: Cooperation in food acquisition is a hallmark of the human species. Given that costs and benefits of cooperation vary among production regimes and work activities, the transition from hunting-and-gathering to agriculture is likely to have reshaped the structure of cooperative subsistence networks. Hunter–gatherers often forage in groups and are generally more interdependent and experience higher short-term food acquisition risk than horticulturalists, suggesting that cooperative labour should be more widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This suggests that's Hrdy's [ 84 ] assertion was well founded, that mothers require large, flexible networks to ensure they receive the help required. Therefore, in line with other contributions to this special issue, women are not constrained to small, dyadic networks [ 1 , 10 , 85 ]. Interestingly, the low-investment networks were large, comprising of, on average, 25 different allomothers over the course of the 3 days of observations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This suggests that's Hrdy's [ 84 ] assertion was well founded, that mothers require large, flexible networks to ensure they receive the help required. Therefore, in line with other contributions to this special issue, women are not constrained to small, dyadic networks [ 1 , 10 , 85 ]. Interestingly, the low-investment networks were large, comprising of, on average, 25 different allomothers over the course of the 3 days of observations.…”
Section: Discussionsupporting
confidence: 54%
“…Overall, while the ‘settled’ and ‘mobile’ Agta communities are part of the same population with a continuous gradient of livelihood change, the flexibility of human childcare is noteworthy, as the identity of the carers did vary. This highlights the flexibility of women's social networks documented here and elsewhere, and demonstrates them as the outcome of demographic trends, gender roles, post-martial residence norms [ 85 ] and different modes of subsistence [ 1 , 10 , 56 ], rather than being constrained. Future research should keep probing the structure of this flexibility to help us better understand the functions of women's social networks and allomothering and how they are expected to change within transitioning populations.…”
Section: Discussionmentioning
confidence: 63%
“…However, they did not find this to be the case for Agta women (Philippine foragers); rather, mothers had large and diverse childcare networks across both mobile and sedentary communities. In a cross-cultural study, Kraft and colleagues ([ 115 ], in this issue) found support for the prediction that the size and composition of cooperative food networks vary with the risks associated with food acquisition strategies. Their comparison of Batek (Malaysian hunter–gatherers) and Tsimane (Bolivian horticulturalists) showed that Batak women, who experienced greater variability in daily foraging success, had more diffuse and diverse networks in contrast to Tsimane women, who relied on fewer, dependable cooperative partners, who were most often close kin, for horticultural labour.…”
Section: Key Themes and Findings From This Issuementioning
confidence: 89%
“…Thus far, to understand such cooperative subsistence practices in humans, extant research has focused on the ways in which men solve the challenges presented during and after collaborative hunting (7,10,(12)(13)(14)(15)(16)(17)(18). Although women's cooperation in subsistence activities-beyond alloparenting and food sharing-has received attention (19)(20)(21)(22)(23)(24)(25)(26)(27), the network structure of women's subsistence groups remains largely understudied [but see (28) for emerging work].…”
Section: Introductionmentioning
confidence: 99%